Differential Evolution Algorithm for Identification of Structural Damage in Steel Beams - Brunno Emidio Sobrinho; Gilberto Gomes; Welington Vital da Silva; Ramon Silva; Erwin U. L. Palechor; Luciano M. Bezerra (Fracture and Structural Integrity)
Problems involving errors and uncertainties from the use of numerical and experimental responses of beams using optimization processes have been studied by many researchers. In this field, to simulate the real behavior of structures, especially in problems involving damage, it is required to have reliable experimental results in order to adjust a numerical model. These difficulties may be associated for example to modeling the connection stiffness, support conditions, or relevant parameters in structures involving damages among others. This paper proposes a new methodology to detect damage in steel beams using the Differential Evolution Technique based on experimental and numerical data. The results show a great potential of the methodology to solve damage detection problems.